2014
DOI: 10.1371/journal.pone.0096764
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Exo1 K589E Polymorphism on Cancer Susceptibility: Evidence Based on a Meta-Analysis

Abstract: The exonuclease1 (Exo1) gene is a key component of mismatch repair (MMR) by resecting the damaged strand, which is the only exonuclease involved in the human MMR system. The gene product is a member of the RAD2 nuclease family and functions in DNA replication, repair and recombination. However, whether Exo1 is required to activate MMR-dependent DNA damage response (DDR) remains unknown, the conclusions of the Exo1 polymorphisms on cancer susceptibility studies were not consistent. We carried out a meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 23 publications
(20 reference statements)
1
10
1
Order By: Relevance
“…However, we found that the data reported by Bayram 41 from the studies by Wang et al 23 and Ibarrola-Villava et al 26 were not the same as the original data. Another recent meta-analysis by Duan et al 42 concluded that the Glu589Lys polymorphism was significantly associated with increased cancer risk in all genetic models, which differed from our own results. This may be explained by the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, we found that the data reported by Bayram 41 from the studies by Wang et al 23 and Ibarrola-Villava et al 26 were not the same as the original data. Another recent meta-analysis by Duan et al 42 concluded that the Glu589Lys polymorphism was significantly associated with increased cancer risk in all genetic models, which differed from our own results. This may be explained by the relatively small sample size.…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, Bayram 41 and Duan et al 42 have conducted meta-analyses to identify whether there was any evidence of a relationship between the Exo1 Glu589Lys polymorphism and cancer susceptibility. Their conclusions could be considered to be inconsistent, which may be partially attributable to the relatively small sample size.…”
Section: Discussionmentioning
confidence: 99%
“…A widely assessed non-synonymous single nucleotide polymorphism (SNP) at codon 589 (rs1047840KE) is closely associated with increased susceptibility to lung cancer [17][18][19], gastric cancer [20], cervical cancer [21], breast cancer [22], oral cancer [23], colorectal cancer [24], glioma [25] and HCC [26]. Such SNP could be used as a biomarker of carcinogenesis [27]. Besides, partly due to the heterogeneity of different cancer types, it remains an open question whether other moderate genetic polymorphisms induce or inverse cancer susceptibility.…”
Section: Introductionmentioning
confidence: 99%
“…This suggested the effect to be ethnicity dependent. 43 We also estimated the allele frequency of both CDH1 (-160C/A) and Exo1 (K589E) SNPs for both prostate cancer cases and controls. Our results demonstrated that the variant A allele in CDH1 (-160C/A) and Exo1 (K589E) genes was significantly associated with increased risk of prostate cancer.…”
Section: Discussionmentioning
confidence: 99%